Peningkatan Kompetensi Guru di Sekolah Dasar Dalam Implementasi Kurikulum Merdeka Belajar - Syafrizal Syafrizal (Journal on Education, 2023)
Teachers have an important role in the development of students. The purpose of this paper is to describe the increase in teacher competence in implementing the independent learning curriculum in elementary schools. This research is a qualitative descriptive study using the literature study method. The literature used is literature that is relevant to the problems and research objectives, such as books, journal articles, proceedings and research reports. To implement independent learning, teachers must master pedagogical skills, skills in adapting teaching styles to student learning styles, skills in mastering online learning, and skills in mastering learning strategies. In addition, the teacher must also master the principles of independent learning, forms of independent learning, and independent learning student learning activities.